Moving Monoliths: Easter Island and Environmental Collapse - Maureen Folk (EXARC Journal)
The Rapa Nui civilization once thrived on Easter Island, and produced unique statues which became a parable for collapse around the world (Hunt and Lipo, 2011). Several experiments have been conducted to better understand this collapse, specifically surrounding the movement of the islands’ largest inhabitants, the moai – the large monolithic human figures carved by the Rapa Nui people. Many people surmise that the ultimate downfall of Easter Island is attributed to the movement of the moai. Some even believed that the natives placed the creation and movement of these statues above their need to survive. The following research focused on the environmental impact of moving the moai on the island. It has been hypothesised by a variety of scholars, including Jo Anne Van Tilburg and Charles Love (Kamrani, 2012), that these multi-ton stone statues were moved horizontally using palm rollers or sleds. Hunt and Lipo (2011) challenged this idea, arguing that the statues were moved in an upright/vertical position. This follows the narrative that the native Rapa Nui people tell –  that the statues "walked" to where they are today. In either scenario, the production and movement of these monoliths would have had an impact on the environment. The goal of this academic research was to decipher the severity of environmental deterioration directly caused by the movement of moai in the upright position using ropes.